Inherent Safety Assessment of a Mass/energy Integrated Large-scale Gasoil Hydrocracking Process - Luisa Acosta-Esalas; Sofia Garcia-Maza; Angel D. Gonzalez-Delgado (Chemical Engineering Transactions)
In this study, an inherent safety analysis of the mass/energy integrated large-scale gas oil hydrocracking process was carried out using the Inherent Safety Index ( ?? ???? ) methodology using Computer Aided Process Engineering (CAPE) tools and Aspen Hysys V.14 simulator. This industrial process was designed to produce high value-added fuels, such as naphtha, kerosene, gasoil and liquefied petroleum gas, using Medium Vacuum Gas Oil (MVGO), Light Cycle Gas Oil (LCGO) and Heavy Coke Gas Oil (HKGO) as fresh feed. The ?? ???? assessment identified risks inherent in the process and proposed areas for improvement. The analysis was based on industry data obtained from mass and energy balances and operating conditions. The ISI integrates the Inherent Chemical Safety Index ( ?? ???? ) and the Inherent Process Safety Index ( ?? ???? ), which, in this case, yielded scores of 28 and 19, respectively, with an overall value of 47. The results indicated that the greatest risks are associated with the handling of compounds such as hydrogen, methane and benzene, whose toxic and flammable properties increase the operational hazard, and with the exothermicity of hydrotreating and hydrocracking reactions. Finally, it was concluded that the risks identified exceed the limits recommended by the regulations, which highlights the need to optimize process safety.